Toward an information management system for handling parenting information users' comments. Issue 1 (2015) - Sherif, Reem El; Roy, Pascale; Tang, David Li; Pluye, Pierre; Bush, Paula; Doray, Geneviève; Lagarde, François
ABSTRACT: Little is known about how their qualitative feedback can be used by information providers. In this study, researchers worked with information providers, 'Naitre et grandir' (N&G), to implement the Information Assessment Method (IAM) for assessing and improving parenting information. Qualitative feedback was collected from participants who visited the N&G website during the study period and who completed an IAM questionnaire. Using an Organizational Participatory Research approach, a coding manual for the identification of participants' comments was created, and developed by the researchers in partnership with information providers. This manual was used by two coders for classifying participants' comments. A 4‐step process was followed. For each step, a sample of comments were codes, coding was compared, and codes were further refined. At step‐4, the inter‐coder reliability was tested. This led to a reliable coding manual that will be used in the creation of an online system to facilitate the coding of comments, and provide selected comments to N&G editors on a weekly basis. This system can be adapted by other website editors.